Pengaruh Arus Kas Operasi dan Ukuran Perusahaan Terhadap Persistensi Laba Pada PT. Plaza Indonesia Realty Tbk - Wulan Rizki Ramdani; Nurul Huda; Nafisah Nurulrahmatiah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to analyze the effect of operating cash flow and firm size on earnings persistence at PT. Plaza Indonesia Realty Tbk. The background of this research is based on the importance of earnings persistence as an indicator of long-term financial performance stability. The independent variables in this study are operating cash flow and firm size, while the dependent variable is earnings persistence. This research uses financial statement data from PT. Plaza Indonesia Realty Tbk for the period 2014-2023, applying multiple linear regression analysis. The results indicate that operating cash flow does not have a significant effect on earnings persistence. Meanwhile, firm size has a significant effect on earnings persistence. Simultaneously, operating cash flow and firm size have a significant effect on earnings persistence. The coefficient of determination is 59.2%, indicating that variations in earnings persistence can be explained by operating cash flow and firm size, while the remaining 40.8% is influenced by other factors not examined in this study. These findings suggest that companies should also pay attention to other financial factors to enhance long-term earnings persistence.